Vascular Endothelial Growth Factor-C (VEGF-C) Expression Can Not Predict Pelvic Lymph Node Metastases and Response to Neo-adjuvant Chemotherapy in Bulky Cervical Cancer - Hutapea, Johnson (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To assess whether VEGF-C expression can predict the response to neoadjuvant chemotherapy and pelvic lymphnode metastases in bulky cevical cancer. Methods: Seventeen cervical cancer stage IB2 and IIA2 cases during the period of July 2009 until June 2010 were collected consecutively and given neoadjuvant chemotherapy (NAC) PVB prior radical surgery. Response to treatment was evaluated based on the change of tumour size. VEGF-C expression was examined immunohistochemically at tumour biopsy before chemotherapy. The presence of lymphnode metastases histopathologically were obtained from pelvic lymphnode dissection. The difference and correlation of response and metastases on VEGF-C expression were analized statistically. The validity of the cut off percentage of immunopositive cells to VEGF-C to identify non responding and metastatic cases was calculated with the ROC. Multivariate analysis were done to determine the predictor of no response to chemotherapy. Results: Clinical response, using the RECIST version 1.1 criteria, was found in 41.18% cases and lymphnode metastases were found in 27.27% cases. VEGF-C was expressed in all cases. Statistically, there were no significant differences and correlation in response to treatment and pelvic lymphnode metastases on VEGF-C expression. At the cut off â¥ 76% immunopositivity to VEGF-C, the sensitivity to identify no response and the specificity to identify response to NAC are 70.00% and 71.43% respectively (LR+ 2.45 and LR- 0.42); whereas at the cut off â¥ 75% immunopositivity to VEGF-C, the sensitivity to identify lymphnode metastases and the specificity to identify no lymphnode metastases are 100.00% and 75.00% (LR+ 4.0 and LR- 0). With multivariate analysis using logistic regression, the cut off â¥ 76% immunopositive cells to VEGF-C were found to have positive coefficient, largest OR and statistic score, 1.93, 6.88 (96% CI OR 0.45; 104.34) and 41 respectively, to predict non responders in a prediction score model. Conclusion: VEGF-C expression on biopsy specimen bulky cervical cancers can not differentiate cases that respond to NAC and metastases to the pelvic lymphnode from that do not. The cut off â¥ 76% immunopositive cells to VEGF-C in a prediction model can be used as an alternative predictor to identify non responders. [Indones J Obstet Gynecol 2012; 36-3: 144-9] Keywords: bulky cervical cancer, neoadjuvant chemotherapy, response and metastases prediction, VEGF-C immunohistochemistry expression